Surfactant-Promoted Prussian Blue Analogues Fabricated Electrodes for Electrocatalytic Water Oxidation - Sana Ibadat,; Hafiza Tauseef Ashfaq,; Ruqia,; Muhammad Adeel Asghar,; Ali Haider,; Saqib Ali, (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2023)
Prussian blue analogues (PBAs) have unique structural and chemical behaviour and therefore have applications in various fields of catalysis as energy conversion materials for storage devices and molecular sensing. Herein we focused on the in-situ synthesis of three PBAs comprising cobalt hexacyanoferrate (CoHCF), nickel hexacyanoferrate (NiHCF), and cobalt-nickel hexacyanoferrate (CoNiHCF) through cation i.e. cetyltrimethylammonium bromide (CTAB) assisted drop cast method. The electrocatalysts were characterized through a multitude of spectroscopic techniques and were tested for water oxidation study. It was found that among the three electrocatalysts, CoNiHCF showed comparatively better catalytic performance with an overpotential value of 570 mV (at 1 mA cm-2).